Stabilization of residual soil with alkali-activated fly ash and inclusion of treated coir fibre - Tan, Teing Teing (2019)
Residual soils have not been always conducive to construction road and other structures. Alkaline activation (AA) is one of the beneficial soil improvement techniques used to improve the geotechnical characteristics of soils with a new generation of cementitious binders. However, soil stabilized with alkali-activated binders will cause to post-peak brittleness. Therefore, coir fibres were incorporated in the stabilized soil as a source of discrete reinforcement to improve the mechanical properties of the soil. The mechanical performance of the reinforced soils depends on the nature of the soil and fibre as well the interaction between the fibre and the alkaline activation stabilized soil. The present work focuses on investigating the use of a locally available by-product (fly ash) as precursor in alkaline activation reactions as well as treated coir fibres as discrete reinforcement. Surface treatment was applied through an agent including linseed oil and turpentine oil in order to improve its durability in alkaline environment as well as tensile strength and to minimize the biodegradable nature of fibre in soil. Moreover, to confirm the alteration of morphology in the fibres and understand the underlying mechanisms of treated fibres, field emission scanning electron microscopy (FESEM) and energydispersive X-ray spectroscopy (EDX) tests were performed. Furthermore, the mechanical properties of soil matrix were assessed. A series of laboratory tests including compaction, unconfined compressive strength tests (UCS), indirect tensile strength tests (ITS), flexural strength tests (FS), direct shear tests (DS) and California bearing ratio tests (CBR) were carried out on original soil, alkali activated stabilized soil, alkali activated stabilized soil reinforced with untreated and treated fibres. The contents were varied from 40% to 70% of dried soil by weight for fly ash and 1% of dried soil by weight for treated coir fibres. The specimens were cured in for 7 and 28 days. The results revealed that the linseed oil treated fibres increased the tensile strength up to 183% compared with untreated fibres. The fibres treated with linseed oil showed higher mechanical performance compared with the fibres treated by turpentine oil. The FESEM/EDX results showed that cellulosic pores of the fibres contain Al and Si which form network like bonds, tightly wrapped around the fibres. The compressive strength, indirect tensile strength and flexural strength of the treated soil increased by 37, 7 and 93%, respectively, when linseed oil treated fibres were used compared with those of alkali activated stabilized soil with untreated fibres. Moreover, the addition of linseed oil-treated fibres increased the shear strength parameters and California bearing ratio of soil. According to the microstructural analysis, the interaction between the fibre surface and the geo-polymeric matrix is the main factor contributing to enhanced behaviour of the reinforced mixtures. This research is important that it confirms that the surface treatment can-not only increase the mechanical performance of coir fibres but also improves the interfacial mechanical interactions between the fibre surface and soil particles, resulting in a higher performance of the composites used as the road subgrade.